The Land Snails of Virginia - Leslie Hubricht (Hello World!, 1971)
This paper lists all of the land snails from Virginia in the collection of the author. These records, for the most part, are from southern and western Virginia; with only scattered records for the northern part of the state. Some fossil records are included, but these are from only two localities in Halifax and Pulaski Counties.